Metabolome and transcriptome analyses identify the characteristics and expression of related saponins of the three genealogical plants of bead ginseng - Ye, Yihan; Ma, Nan; Peng, Yidan; Chen, Ying; Zhang, Yuqu; Zhao, Shuyan; Ren, Wei; Yan, Yonggang; Zhang, Gang; Yang, Xinjie; Peng, Xiujuan (PeerJ, 2023)
Objective The classification and clinical usage of the different species of bead ginseng are often confused. Therefore, we conducted an integrated metabolomics and transcriptome analysis of three main species of Panax, including Panax japonicas, Panax pseudoginseng, and Panax pseudo-ginseng var. elegantior. Methods A broad metabolome and transcriptome analysis for three origins of bead ginseng plants was performed using UPLC-ESI-MS/MS, RNA sequencing and annotation, and bioinformatic analysis of transcriptome data. Results The levels of 830 metabolites were determined. A total of 291 differentially accumulated metabolites (DAMs) between Panax pseudo-ginseng var. elegantior and Panax japonicas (Group A), with 73 upregulated and 218 downregulated. A total of 331 DAMs (110 upregulated and 221 downregulated) were found between Panax pseudoginseng and Panax japonicas (group B). There were 160 DAMs (102 up-regulated and 58 down-regulated) between Panax pseudoginseng and Panax pseudo-ginseng var. elegantior (group C). In addition, RNA sequencing was performed in the above three ways. A total of 16,074 differential expression genes (DEGs) were detected between Group A, in which 7,723 genes were upregulated and 8,351 genes were downregulated by RNA sequencing. Similarly, 15,705 genes were differentially expressed between group B, in which 7,436 genes were upregulated and 8,269 genes were downregulated. However, only 1,294 genes were differentially expressed between group C, in which 531 genes were upregulated and 763 genes were downregulated. We performed differential gene analysis on three groups of samples according to the Venn diagram and found that 181 differential genes were present. A total of 3,698 and 2,834 unique genes were in groups A and B, while 130 unique genes were in group C. Conclusions This study provides metabolome and transcriptome information for three bead ginseng plants. The analysis of the metabolite content showed differences in the attributes of the three bead ginseng, contained mainly flavonoids, phenolic acids as well as terpenes.
Keywords: Metabolome; Transcriptome; Saponins; Panax japonicas; Panax pseudoginseng; Panax pseudo-ginseng var. elegantior